Oral Health Impact Profile and Associated Variables in Southern Brazilian Drug Users - Susan Jaccoud Ribeiro DE SOUZA; Andrea de Castro DOS SANTOS; Milena Binhame ALBINI; Marilisa Carneiro Leão GABARDO; Antonio Adilson Soares DE LIMA; Maria Ângela Naval MACHADO (Iranian Journal of Public Health, 2018)
Background: This study investigated the association between sociodemographic, behavioral, oral health, variables of drug consumption, and the short version of the Oral Health Impact Profile (OHIP-14), in Southern Brazilian drug users.